2010
DOI: 10.1088/0004-6256/140/5/1254
|View full text |Cite
|
Sign up to set email alerts
|

Mid-Infrared Evidence for Accelerated Evolution in Compact Group Galaxies

Abstract: Compact galaxy groups are at the extremes of the group environment, with high number densities and low velocity dispersions that likely affect member galaxy evolution. To explore the impact of this environment in detail, we examine the distribution in the mid-infrared (MIR) 3.6 − 8.0 µm colorspace of 42 galaxies from 12 Hickson compact groups in comparison with several control samples, including the LVL+SINGS galaxies, interacting galaxies, and galaxies from the Coma Cluster. We find that the HCG galaxies are … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
73
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(81 citation statements)
references
References 34 publications
8
73
0
Order By: Relevance
“…Our results are also consistent with previous studies of the galaxy SFR in compact groups, such as Walker et al (2010) and Tzanavaris et al (2010). The differences between the luminosity function of galaxies in CGs and LGs also support a scenario where low luminosity galaxies merge efficiently leading to both a smaller Fig.…”
Section: Conclusion and Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our results are also consistent with previous studies of the galaxy SFR in compact groups, such as Walker et al (2010) and Tzanavaris et al (2010). The differences between the luminosity function of galaxies in CGs and LGs also support a scenario where low luminosity galaxies merge efficiently leading to both a smaller Fig.…”
Section: Conclusion and Discussionsupporting
confidence: 94%
“…Deng et al (2008) compared the properties of CGs, isolated, and field galaxies and found that, in dense regions, galaxies have A&A 543, A119 (2012) preferentially greater concentration indexes and early-type morphologies. There have been numerous studies of the star formation in CGs: Walker et al (2010) suggested that the compact group environment accelerates the evolution of galaxies from star-forming to quiescent; Bitsakis et al (2010) found a connection between dynamical state and the star formation rate (SFR) in the sense that old CGs host late-type galaxies with slightly lower specific star formation rates than in dynamically young groups; Johnson et al (2007) also found a connection between the star formation and the global properties of groups. Tzanavaris et al (2010) estimated the SFR using both ultraviolet and infrared information and found that the compact group environment accelerates the galaxy evolution by enhancing the star formation processes and favouring a fast transition to quiescence.…”
Section: Introductionmentioning
confidence: 99%
“…However, our test indicates that this is not the main mechanism. Recent studies, based on UV and IR data, have also found a bimodality (gap) in the distribution of SSFR in HCG galaxies and suggested that the high-density environment of CGs has accelerated the evolution of galaxies, transforming star-forming galaxies into quiescent galaxies (Johnson et al 2007;Tzanavaris et al 2010;Walker et al 2010;Bitsakis et al 2010Bitsakis et al , 2011. According to our analysis, galaxies in the HCG have shorter SFTS than in the CIG because they have experienced higher astration rates.…”
Section: Discussionsupporting
confidence: 62%
“…This in turn likely leads to fast consumption of the available gas and abrupt quenching. The observational signatures of this are "gaps" both in mid-infrared colors (Johnson et al 2007;Walker et al 2010Walker et al , 2012 as well as massnormalized star formation rates (specific SFRs, sSFRs, Tzanavaris et al 2010;L. Lenkic et al 2015, in preparation).…”
Section: Introductionmentioning
confidence: 99%